Meningkatkan hasil belajar dengan AI: Studi efektivitas dan implementasi - Ramadan, Alhubul Austad (Maliki Interdisciplinary Journal, 2024)
In the rapidly evolving digital era, artificial intelligence (AI) offers significant potential to revolutionize education by providing more personalized, adaptive, and efficient learning approaches. This study examines the effectiveness of using AI to enhance student learning outcomes through an analysis of various implementations and case studies from educational institutions that have adopted this technology. The research finds that AI can increase student engagement, provide real-time feedback, and tailor learning materials to individual needs. However, challenges such as data quality, privacy, and infrastructure readiness need to be addressed to maximize the benefits of AI. By offering practical recommendations for educators and policymakers, this study aims to promote responsible and sustainable adoption of AI in education.